Report of 6 Cases with Polymyalgia Rheumatica and a Review of the Literatures - Nagura, Hiroshi; Tomonaga, Masanori; Kanemaru, Kazutomi; Ooyama, Toshiro (Nihon Rōnen Igakkai zasshi, 1986)
Polymyalgia rheumatica (PMR) is a clinical syndrome of unknown cause that rarely occurs in persons less than 50 years old. Although the underlying pathological abnormality in PMR is not known, the association with vasculitis linked with the immunological abnormality is well established. The syndrome is characterized by aching and stiffness in the proximal portion of the extremities and torso, along with evidence of an underlying systemic inflammatory reaction. The latter is manifested by loss of weight, low grade fever, arthralgia and laboratory findings such as high ESR and increase of serum acute phase reactant. The clinical features and the laboratory findings of 6 aged patients with polymyalgia rheumatica, identified in our hospital during 9 year period 1975 to 1984, according to Hamrin's criteria, were characterized, comparing with those of the cases previously reported. Clinical and laboratory findings generally were similar to those in earlier studies except the lower frequency of temporal arteritis; Temporal artery biopsy (2 cases) or muscle biopsy (4 cases) were done and negative results. 2 cases among 6 cases, associated with dementia of vascular type or ptosis with external ophthalmoplegia, were also described in detail and discussed as to the possibility of the association of vasculitis. Immunological exams also did not support the previous studies suggesting that PMR might be linked with immunological abnormality.